How First Peoples Principles of Learning Have Been Included in British Columbia Offshore School Inspection Reports From 2018 to 2024 - Alexander, Ian (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2026)
This article examines how British Columbia (BC) offshore schools integrate First Peoples Principles of Learning into the BC curriculum taught in these schools located outside Canada. BC offshore schools are in 12 countries and use the same curriculum as in BC. Students who graduate from offshore schools earn the same diploma as Canadians and often attend universities in Canada. A substantial change in the revised BC curriculum was the inclusion of Indigenous perspectives and knowledge with First Peoples Principles of Learning being one of the resources to integrate this knowledge in all courses through the curriculum. This study used content analysis and critical discourse analysis to examine text segments in 282 inspection reports published each year by the BC government. Findings indicate that BC offshore schools have shown uptake and expanded inclusion of Indigenous perspectives but mostly confined to these principles of learning as a portion of the new curriculum.